From rebel to rabbi: reclaiming Jesus and the making of modern Jewish culture - Hoffman, Matthew B. (Stanford studies in Jewish history and culture, 2007)
Jesus and the Jewish question -- The quest for the Jewish Jesus -- The crucifix question -- Yiddish modernism and the landscape of the cross -- The passion of Jewish history -- The artist crucified -- The Jesus question revisited